2017
DOI: 10.1016/j.jbiomech.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Human cochlear hydrodynamics: A high-resolution μCT-based finite element study

Abstract: Measurements of perilymph hydrodynamics in the human cochlea are scarce, being mostly limited to the fluid pressure at the basal or apical turn of the scalae vestibuli and tympani. Indeed, measurements of fluid pressure or volumetric flow rate have only been reported in animal models. In this study we imaged the human ear at 6.7 and 3-μm resolution using μCT scanning to produce highly accurate 3D models of the entire ear and particularly the cochlea scalae. We used a contrast agent to better distinguish soft f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In the present study, we did not model the movement of the inner ear fluids or blood perfusion within the cochlea. Several studies have confirmed the presence of local and temporal pressure gradients that may be important factors contributing to heat transfer (De Paolis et al 2017; Olson 1999; Salt et al 2001; Salt et al 1986). The present model also does not take into account differences in soft and hard tissues in the human ear and may benefit from higher resolution, micro-computer tomography (CT) geometric model (De Paolis et al 2017; Manoussaki and Chadwick 2000).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, we did not model the movement of the inner ear fluids or blood perfusion within the cochlea. Several studies have confirmed the presence of local and temporal pressure gradients that may be important factors contributing to heat transfer (De Paolis et al 2017; Olson 1999; Salt et al 2001; Salt et al 1986). The present model also does not take into account differences in soft and hard tissues in the human ear and may benefit from higher resolution, micro-computer tomography (CT) geometric model (De Paolis et al 2017; Manoussaki and Chadwick 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have confirmed the presence of local and temporal pressure gradients that may be important factors contributing to heat transfer (De Paolis et al 2017; Olson 1999; Salt et al 2001; Salt et al 1986). The present model also does not take into account differences in soft and hard tissues in the human ear and may benefit from higher resolution, micro-computer tomography (CT) geometric model (De Paolis et al 2017; Manoussaki and Chadwick 2000). Finally, based upon our previously published experiments in the rat model of cochlear implantation (Tamames et al 2016), we developed the hypothermia protocol to incorporate rewarming the cochleae to baseline temperature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The risk of perilymph leakage can be mitigated by plugging fascia to RWM perforations, but the outcome is unpredictable. 104 , 105 Another unwanted effect observed in intra-cochlear administration is restricted viral distribution secondary to the low flow rate of cochlear fluid in adult mice. After RWM injection, a high local concentration of viral vectors was found with an efficiency gradient from base to apex due to slow distribution and subsequently, poor transduction leading to a high therapeutic concentration in the basal area but sub-therapeutic in the apical area.…”
Section: Delivery Routesmentioning
confidence: 99%
“…Optimal designed ossicular prosthesis and cochlear implant electrodes, as well as their precise insertion are possible thanks to the development of computer-aided engineering (CAE) and computer-aided surgery (CAS): design of the ossicular prosthesis and cochlear implant electrodes is greatly simplified by computer-aided design (CAD) [4,5]; afterwards verification and optimization of them are achieved by finite element method (FEM) [6,7,10]; due to the complexity and small scale of the structure of the middle and the inner ear, CAS is usually applied in preoperative surgery planning and navigation during the surgery [8,9].…”
Section: Introductionmentioning
confidence: 99%